Socioeconomic indicators related to the global burden of breast cancer in women in 2020: an analysis of WHO data - Tingting XU; Ruoyu YANG; Jingjing LI; Yiying FANG (Zhongguo gonggong weisheng)
ObjectiveTo understand the socioeconomic factors that influence the global burden of breast cancer in women and to provide a reference for further optimization of breast cancer prevention, screening, and treatment strategies. MethodsData on the global age-standardized incidence rate (standardized incidence rate) and global age-standardized mortality rate (standardized mortality rate) of breast cancer in women from 175 countries around the world in 2020 were collected from the World Health Organization's Cancer Tomorrow database. The breast cancer mortality to incidence ratio (MIR), a quantitative indicator of the burden of breast cancer, was calculated. Ten indicators representing national socioeconomic development were selected from the World Health Statistics 2020 and the Human Development Report 2020. Correlation analysis and multiple linear regression models were used to analyze the socioeconomic factors influencing the global burden of breast cancer in women. ResultsIn 2020, the average standardized incidence rate, standardized mortality rate, and MIR of breast cancer among women in 175 countries worldwide were 49.39 ± 22.35/100 000, 13.85 ± 5.48/100 000, and 0.33 ± 0.15%, respectively. The mean values of the 10 selected indicators representing national socioeconomic development were as follows: 2 138.06 ± 7 465.03 million for total female population, 26.58 ± 17.12 μg/m3 for mean annual urban particulate matter concentration; 63.97 ± 57.32 per 10 000 population for density of physicians, 4.01 ± 4.11 per 10 000 population for density of pharmacists, 4.11 ± 4.32 US dollars for net official development assistance received by the medical research and basic health sector per capita, 63.65 ± 20.31 for average of 13 International Health Regulations Core Capacity Scores, 10. 41 ± 5.17% for the percentage of government health expenditure, 68.00 ± 28.65% for the percentage of the population using safely managed sanitation services, 66.05 ± 95.28 million US dollars in official development assistance (ODA) provided through government-coordinated expenditure plans specifically for water and sanitation, and 0.587 ± 0.190 for the inequality-adjusted Human Development Index (HDI). Correlation analysis showed that the global MIR of breast cancer in women was positively correlated with urban particulate matter (r = 0. 480) and net ODA per capita (r = 0. 516) (both P < 0. 001) and negatively correlated with physician density (r = – 0.782), pharmacist density (r = – 0.639), average core capacity score (r = – 0.635), percentage of government health expenditure (r = – 0.614), population using sanitation services (r = – 0.624), and HDI (r = – 0.900) (all P < 0.001). Multiple linear regression analysis showed that net ODA per capita had a positive effect on the female breast cancer burden (β = 0.003, 95% confidence interval [95%CI]: 0.002 – 0.007), while total female population (β = – 0.004, 95%CI: – 0.005 to – 0.003), physician density (β = – 0.007, 95%CI: – 0.008 to – 0.006), pharmacist density (β = – 0.026, 95%CI: – 0.030 to – 0.021), average core capacity score (β = – 0.005, 95%CI: – 0.006 to – 0.004), and HDI (β = – 0.873, 95%CI: – 0.906 to – 0.574) had negative effects. ConclusionThe global burden of breast cancer in women is influenced by a variety of socioeconomic factors, including the macroeconomic level, the efficiency of health resource allocation, national investments in public health, and the social environment.